2021
DOI: 10.48550/arxiv.2103.02902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stochastic measure-valued models for populations expanding in a continuum

Abstract: We model spatially expanding populations by means of a spatial Λ-Fleming Viot process (SLFV) with selection : the k-parent SLFV. We fill empty areas with type 0 "ghost" individuals, which have a strong selective disadvantage against "real" type 1 individuals. This model is a special case of the SLFV with selection introduced in [19,22] : natural selection acts during all reproduction events, and the fraction of individuals replaced during a reproduction event is constant equal to 1. Letting the selective ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The ∞-parent spatial Λ-Fleming Viot process, or ∞-parent SLFV, was introduced in [32] as a model for expanding populations in R 2 . Its main feature is the use of "ghost" individuals (thereafter referred to as "type 0" individuals) to fill empty areas, adapting ideas from [13,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ∞-parent spatial Λ-Fleming Viot process, or ∞-parent SLFV, was introduced in [32] as a model for expanding populations in R 2 . Its main feature is the use of "ghost" individuals (thereafter referred to as "type 0" individuals) to fill empty areas, adapting ideas from [13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Its main feature is the use of "ghost" individuals (thereafter referred to as "type 0" individuals) to fill empty areas, adapting ideas from [13,23]. In [13,23,32], ghost individuals can reproduce as well, modelling stochastic fluctuations in population sizes, but with a selective disadvantage against real individuals (thereafter referred to as "type 1" individuals), ensuring that population expansions can indeed occur. In [32], it is shown that the ∞-parent SLFV corresponds to the limit of an SLFV with strong selection when the selective advantage of type 1 individuals over type 0 individuals becomes infinitely strong.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to incorporate extinction event-induced fluctuations in a Wright-Fisher model, it is possible to adopt the approach used in [13,22]: assign a maximal population size to each patch, and fill the remaining space with "ghost", or type 0, individuals. In this framework, each patch contains both type 1 "real" individuals and type 0 "ghost" individuals, the former having a very strong selective advantage over the latter (in the spirit of [30]).…”
Section: Introductionmentioning
confidence: 99%